Timber and timber trees, native and foreign - Laslett, Thomas (Macmillan, 1894)
The author tackles his subject firstly in three sections: 'On Timber in General', 'The Timber of Dicotyledonous Tress' and 'Coniferous Timber Trees', followed by appendices on uses of timber, tensile and vertical strength, elasticity and transverse strength, and more.